Small and Long Non-coding RNAs as Functional Regulators of Bone Homeostasis, Acting Alone or Cooperatively - Mateusz Sikora; Krzysztof Marycz; Agnieszka Smieszek (Elsevier, 2020)
Emerging knowledge indicates that non-coding RNAs, including microRNAs (miRNAs) and long-noncoding RNAs (lncRNAs), have a pivotal role in bone development and the pathogenesis of bone-related disorders. Most recently, miRNAs have started to be regarded as potential biomarkers or targets for various sets of diseases, while lncRNAs have gained attention as a new layer of gene expression control acting through versatile interactions, also with miRNAs. The rapid development of RNA sequencing techniques based on next-generation sequencing (NGS) gives us better insight into molecular pathways regulated by the miRNA-lncRNA network. In this review, we summarize the current knowledge related to the function of miRNAs and lncRNAs as regulators of genes that are crucial for proper bone metabolism and homeostasis. We have characterized important non-coding RNAs and their expression signatures, in relationship to bone. Analysis of the biological function of miRNAs and lncRNAs, as well as their network, will pave the way for a better understanding of the pathogenesis of various bone disorders. We also think that this knowledge may lead to the development of innovative diagnostic tools and therapeutic approaches for bone-related disorders.